Cone beam computed tomographic analysis of the position and course of the mandibular canal - Domínguez-Mejía, José; Ruge-Jiménez, Omar; Aguilar-Méndez, Germán; Ñáñez-López, Óscar; Oliveros-Torres, Guillermo (Revista Facultad de Odontología Universidad de Antioquia, 2010)
Introduction: surgical procedures involving the mandible require a deep understanding of the position and course of the inferior alveolar conduct (IAC) that encloses the inferior alveolar nerve. Computerized volumetric tomography (CVT) is an under used diagnostic tool in our context, mostly because of the costs it compels, nevertheless it’s a sensitive and precise method for the evaluation of IAC above other diagnostic current tools. Method: 50 last generation computerized volumetric tomographies, using Cone Beam technology, were evaluated in 18 years old patients or older, with premolars and molars present, without any evident maxillary anomalies, mandibular pathology or alteration that decrease bone quality. Panoramic and transectional cuts were performed. Results: the average distance from IAC to alveolar crest was 17.9 mm for women and 19.8 mm for men. The average distance from IAC to the vestibular plate was 3.8 mm for both genders towards the lingual plate, the distances from IAC was 3,2mm for women and 2.8 mm for men. The average distance from basilar border to IAC was 6.5 mm for women and 6.2 mm for men. From the mandibular foramen to anterior border of mandibular ramus, the average distance for men was 13.2 mm and 12.3 mm for women. Conclusion: CVT is a highly sensitive diagnostic tool for the assessment of IAC position and course. There were no differences regarding age or between both sides of the mandible among the three measured points on the mandibular body.